2008
DOI: 10.4314/ajtcam.v4i3.31230
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycemic Effects Of Separate And Composite Extract Of Root Of <i>Musa paradisiacal</i> And Leaf Of <i>Coccinia indica</i> In Streptozotocin-Induced Diabetic Male Albino Rat.

Abstract: We evaluated the antihyperglycaemic properties of aqueous-methanolic (40:60) extract of root of Musa paradisiaca and leaf of Coccinia indica in separate as well as in composite manner by conducting experiment on streptozotocin-induced diabetic rats. We measured food and water intake ability, the fasting blood glucose level, glucose tolerance, activities of important carbohydrate metabolic enzymes like glucose-6-phosphatase, glucose-6phosphate dehydrogenase, hexokinase in liver along with quantification of glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
22
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 24 publications
7
22
0
1
Order By: Relevance
“…Hence, the need to reduce the risk of vascular complications by securing adequate glycemic, lipidemic, blood pressure and weight control [6]. Currently diabetes is controlled by diet, exercise, oral hypoglycemic agents and insulin therapy [7]. The high level of treatment failures, unpleasant side effects and enormous cost associated with diabetic therapy have generated an urgent need and desire for alternative treatments [8].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the need to reduce the risk of vascular complications by securing adequate glycemic, lipidemic, blood pressure and weight control [6]. Currently diabetes is controlled by diet, exercise, oral hypoglycemic agents and insulin therapy [7]. The high level of treatment failures, unpleasant side effects and enormous cost associated with diabetic therapy have generated an urgent need and desire for alternative treatments [8].…”
Section: Introductionmentioning
confidence: 99%
“…[4344] Treatment with ‘ Diashis ’ or ‘Glibenclamide’ in diabetic rats resulted in a significant recovery in hemoglobin and HbA 1c levels, which may be due to recovery in plasma glucose towards the control levels.…”
Section: Discussionmentioning
confidence: 99%
“…Roots of Musa paradisiaca are antihelmintic, flowers are astringent and fruits are mild laxative. It is also useful in celiac disease, constipation and peptic ulcer (Mallick et al, 2007). It has been found that bananas have curative properties both scientifically and traditionally.…”
Section: Introductionmentioning
confidence: 99%